A comparative study of family burden between alcohol dependent patients and patients with schizophrenia - Nath, Subhashish; Nath, Kamal (Asian Journal of Medical Sciences, 2021)
Background: Alcohol dependence and Schizophrenia are two major psychiatric illnesses posing considerable burden on the families and caregivers. Alcohol dependence, like Schizophrenia, tends to run a chronic and erratic course causing a significant burn out on the families. Aims and Objectives: 1. To describe the Socio-demographic characteristics of Alcohol dependent patients and patients with Schizophrenia. 2. To compare the family burden in patients with Alcohol dependence and patients with Schizophrenia. Materials and Methods: The study was conducted in the Department of Psychiatry of a tertiary institute of north eastern India over a period of one year. A total of 100 cases (50 each of Alcohol dependence and Schizophrenia) constituted the study sample. A Semi-structured proforma was used for socio-demographic variables. The assessment of family burden was done using Pai and Kapur Family Burden Interview Schedule. Results: The two groups differed significantly from each other with respect to most of the sociodemographic variables. The overall family burden in the alcohol dependent patients was significantly higher than in schizophrenia patients. Conclusion: The families of both Schizophrenia and alcohol dependent patients suffer from moderate to severe amount of burden in various dimensions of their lives and the burden experienced by the families of alcohol dependent patients is in no way lesser than a chronic debilitating illness like Schizophrenia.